2006
DOI: 10.1203/01.pdr.0000214992.69847.6f
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Behavior and Attentional Capacity after Adenotonsillectomy

Abstract: ABSTRACT:The objective of this study was to quantify behavioral and attention capacity changes in children aged 4 -11 y before and 3 mo after adenotonsillectomy (A/T). Overnight cardiorespiratory recordings were performed in 61 "behaviorally normal" children 1 wk before A/T. Tests of sustained attention using visual and auditory continuous performance tests (CPT) were completed by children 1 wk before and 3 mo after A/T. Behavioral Assessment Scales for Children (BASC) and a sleep questionnaire were completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 30 publications
1
31
0
1
Order By: Relevance
“…Learning, memory, and visuospatial skills 226 Kaemingk et al 33 Kennedy et al 34 Kurnatowski et al 227 Carvalho et al 228 III 1332 Objective measures of general intelligence, verbal skills affected by SDB Montgomery-Downs et al 50 Suratt et al 43 Friedman et al 26 II 45 Additive factors were SES and ethnicity 42 , 45 or BMI, 42 , 45 , 47 which contributed to findings of poor school performance in SDB Kaemingk et al 33 Ng et al 219 Perez-Chada et al 220 Shin et al 47 Urschitz 232 Kaemingk et al 33 Kennedy et al 34 Kurnatowski et al 227 O'Brien et al 233 Spruyt et al 234 Giordani et al 38 Halbower et al 28 233 Objective testing performed in all studies Perez-Chada et al 220 Honaker et al 235 Lundeborg et al 51 Suratt et al 43 III 236 Galland et al 237 Gottlieb et al 213 Hamasaki Uema et al 232 Kaemingk et al 33 Li et al 238 Mulvaney et al 32 Urschitz et al 229 Chervin et al 37 I 105 O'Brien et al 24 I 118 Visual and auditory attention and working memory. Executive functions are required for optimal school performance and are acquired through adolescence in developing children.…”
Section: Cognitive Deficitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Learning, memory, and visuospatial skills 226 Kaemingk et al 33 Kennedy et al 34 Kurnatowski et al 227 Carvalho et al 228 III 1332 Objective measures of general intelligence, verbal skills affected by SDB Montgomery-Downs et al 50 Suratt et al 43 Friedman et al 26 II 45 Additive factors were SES and ethnicity 42 , 45 or BMI, 42 , 45 , 47 which contributed to findings of poor school performance in SDB Kaemingk et al 33 Ng et al 219 Perez-Chada et al 220 Shin et al 47 Urschitz 232 Kaemingk et al 33 Kennedy et al 34 Kurnatowski et al 227 O'Brien et al 233 Spruyt et al 234 Giordani et al 38 Halbower et al 28 233 Objective testing performed in all studies Perez-Chada et al 220 Honaker et al 235 Lundeborg et al 51 Suratt et al 43 III 236 Galland et al 237 Gottlieb et al 213 Hamasaki Uema et al 232 Kaemingk et al 33 Li et al 238 Mulvaney et al 32 Urschitz et al 229 Chervin et al 37 I 105 O'Brien et al 24 I 118 Visual and auditory attention and working memory. Executive functions are required for optimal school performance and are acquired through adolescence in developing children.…”
Section: Cognitive Deficitsmentioning
confidence: 99%
“…There were 9 recent level III or IV studies, most of which showed a correlation between the presence/ 40 Galland et al 237 Golan et al 239 Gottlieb et al 213 Johnson and Roth 45 LeBourgeois et al 230 Mitchell and Kelly 240 Owens et al 189 Roemmich et al 191 Urschitz et al 229 Montgomery 240 Mitchell and Kelly 241 Rudnick and Mitchell 242 Suratt et al 43 III 114 O'Brien et al 24 I 118 Behavior problems, general Goldstein et al 55 IV 1946 Behavior generally measured by using parent questionnaire Goldstein et al 243 Hogan et al 48 Li et al 238 Mitchell and Kelly 241 Mulvaney et al 32 Owens et al 189 Roemmich et al 191 Rosen et al 244 Rudnick and Mitchell 242 Tran et al 58 Wei et al 245 Aggression, oppositional and social problems…”
Section: Cardiovascular Effects Of Osasmentioning
confidence: 99%
“…11,13,46 The tests used in this study may also be suboptimal for detecting effects of AT; measures placing greater demands on sustained attention and novel problem solving may have been more sensitive to the effects of AT. 11,14,22,26,43,47 Although OSAS measures in the study were those routinely used in clinical settings and scored using rigorous approaches, alternative measures of OSAS or sleep disruption may also provide more sensitive indices of the effects of AT on sleep. 7,8,16,17,20,48 A secondary aim was to explore associations of baseline test scores …”
mentioning
confidence: 99%
“…(6)(7)(8)(9)(10)(11)(12) Identification of children at high risk for SDB and its associated morbidities is particularly important given the growing body of evidence that treatment with adenotonsillectomy may improve quality of life and neurocognitive function. (5,(13)(14)(15)(16)(17) Preterm infants are especially vulnerable both to SDB and its sequelae. In a Finnish cohort study, very low birth weight infants were shown to have a two-fold risk of SDB as young adults.…”
mentioning
confidence: 99%